Dynamic alterations in PD-1/PD-L1 expression level and immune cell profiles based on radiation response status in mouse tumor model - Yoon, Yi Na; Choe, Min Ho; Kong, Moonkyoo; Chung, Weon Kuu; Kim, Jae-Sung; Lim, Yu Jin (Frontiers in Oncology, 2022)
Introduction Based on the immunologic effects of anti-cancer treatment and their therapeutic implications, we evaluated radiotherapy (RT)-induced dynamic alterations in programmed death-1 (PD-1)/PD ligand-1 (PD-L1) expression profiles. Methods Local RT with 2 Gy × 5 or 7.5 Gy × 1 was administered to the CT26 mouse model. Thereafter, tumors were resected and evaluated at the following predefined timepoints according to radiation response status: baseline, early (immediately after RT), middle (beginning of tumor shrinkage), late (stable status with RT effect), and progression (tumor regrowth). PD-1/PD-L1 activity and related immune cell profiles were quantitatively assessed. Results RT upregulated PD-L1 expression in tumor cells from the middle to late phase; however, the levels subsequently decreased to levels comparable to baseline in the progression phase. RT with 2 Gy × 5 induced a higher frequency of PD-L1+ myeloid-derived suppressor cells, with a lesser degree of tumor regression, compared to 7.5 Gy. The proportion of PD-1+ and interferon (IFN)-γ+CD8α T cells continued to increase. The frequency of splenic PD-1+CD8+ T cells was markedly elevated, and was sustained longer with 2 Gy × 5. Based on the transcriptomic data, RT stimulated the transcription of immune-related genes, leading to sequentially altered patterns. Discussion The dynamic alterations in PD-1/PD-L1 expression level were observed according to the time phases of tumor regression. This study suggests the influence of tumor cell killing and radiation dosing strategy on the tumor immune microenvironment.